Kinetic, thermodynamic and chemical reaction analyses of typical surgical face mask waste pyrolysis. (1st December 2021) - Sun, Sijia; Yuan, Yougen; Chen, Ruiyu; Xu, Xiaokang; Zhang, Deyuan
Highlights: The surgical mask waste pyrolysis may be regarded as a one-step reaction. The mean reaction rate changes little with heating rate. The mean E and A values are 237.19 kJ/mol and 1.36 × 10 14 min −1, respectively. The suitable reaction model characterizing the pyrolysis is g ( α ) = (−ln(1− α )) 2/3 . Alkanes, alkenes, carbon dioxide, aldehydes, carbon monoxide are mainly detected. Abstract: The epidemic of Corona Virus Disease 2019 (COVID-19) has led to the generation of a large number of waste surgical masks. In recent years, pyrolysis is considered to be an environmental-friendly and efficient method to dispose such solid waste. In this work, the thermal degradation behaviors, kinetic parameters, thermodynamic parameters, pyrolytic products and chemical reactions of typical surgical face mask waste were studied using thermogravimetric analysis (TGA) and Fourier transform infrared (FTIR)-mass spectrometry (MS) analysis in inert atmosphere. It is concluded that the surgical face mask waste pyrolysis in nitrogen can be considered to be a one-step reaction. In addition, the mean E (activation energy) value and the mean A (pre-exponential factor) value are 237.19 kJ/mol and 1.36 × 10 14 min −1, respectively. g ( α ) = (−ln(1- α )) 2/3 (reaction model) may be utilized to characterize the surgical face mask waste pyrolysis in nitrogen. The above kinetic parameters are capable to estimate the surgical face mask waste pyrolysis behaviors in nitrogen. Thermodynamic parameters suggest that the surgical face mask waste pyrolysis can be considered to be an endothermic and non-spontaneous reaction. Inorganic substances, alkanes, alkenes, naphthenic hydrocarbons, aldehydes and ketones are the major volatile products. The amount of the aliphatic compounds is the highest. Specific chemical reactions generating these volatile products are proposed.